The effect of Aronia melanocarpa extract on the phospholipid composition of the rat myocardium during stress - Shvets, V. M.; Maslak, H.; Davydov, V.; Berest, H. H.; Nosulenko, I. S.; Швець, Володимир Миколайович; Берест, Галина Григорівна; Носуленко, Інна Степанівна (My University, 2022)
The research was performed on 80 male rats of the Wistar line. Animals of two age groups were used: adults (10–12 months) and old (22–25 months). The obtained data show that the development of immobilization stress in adult and aged rats are accompanied by the formation of a characteristic complex of changes in the phospholipid composition of the myocardium. Intraperitoneal injection of the chokeberry extract (Aronia melanocarpa) at a dose of 0.2 g/kg 60 minutes before the immobilization has limited stress modulation of myocardial phospholipid composition in aged animals. Thus, the extract of Aronia melanocarpa increases the myocardial resistance to the injury effect of stress.
Keywords: aging; immobilization; myocardium; Aronia melanocarpa